Designing new diagnostic systems for the early detection of tobacco-associated chronic renal damage in patients of a primary care centre in Salamanca, Spain: an observational, prospective study protocol - Luis Garcia-Ortiz; Manuel A Gómez-Marcos; Marta Prieto; Laura Vicente-Vicente; Alfredo G Casanova; Maria Teresa Hernández-Sánchez; Ana Isabel Morales; Moisés Pescador Garriel; Ángela de Cabo Laso; Jesús González Sánchez; Natalia Sánchez Aguadero; Carmela Rodríguez Martín; et al. (BMJ Open, 2020)
Introduction Tobacco causes kidney damage that can progress to chronic kidney disease. However, the diagnostic parameters used in clinics are not effective in identifying smokers at risk. Our first objective is to more effectively detect subclinical renal damage in smokers. In addition, we hypothesise that tobacco consumption can predispose smokers to renal damage on exposure to other potentially nephrotoxic events (drugs, diagnostic procedures and so on). We will test this hypothesis in our second objective by investigating whether certain predisposition markers (GM2 ganglioside activator protein (GM2AP), transferrin and t-gelsolin) are able to detect smokers who are predisposed to kidney damage. Finally, in our third objective, we will study whether smoking cessation reduces subclinical and/or predisposition to renal damage.Methods and analysis For our first objective, a prospective cross-sectional study will be carried out with patients from a primary healthcare centre. The influence of tobacco on renal damage, in patients both with and without additional risk factors, will be studied using a panel of early biomarkers (albuminuria, N-acetyl-beta-D-glucosaminidase, kidney injury molecule-1 and neutrophil gelatinase-associated lipocalin). For our second objective, a prospective longitudinal study will be carried out with patients recruited for our first objective. We will study whether certain predisposition biomarkers (GM2AP, transferrin and t-gelsolin) are able to detect smokers predisposed to renal damage. For our third objective, a prospective longitudinal study will be carried out with patients from a smoking cessation unit. We will study the evolution of the markers described above following smoking cessation.Ethics and dissemination The study has been approved by the Clinical Research Ethics Committee of the Healthcare Area of Salamanca. All study participants will sign an informed consent form in compliance with the Declaration of Helsinki and the WHO standards for observational studies. Results will be presented at conferences and submitted to peer-reviewed journals.Trial registration number NCT03850756.